2014
DOI: 10.1016/j.apgeochem.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Mine tailings dams: Characteristics, failure, environmental impacts, and remediation

Abstract: On a global scale demand for the products of the extractive industries is ever increasing. Extraction of the targeted resource results in the concurrent production of a significant volume of waste material, including tailings, which are mixtures of crushed rock and processing fluids from mills, washeries or concentrators that remain after the extraction of economic metals, minerals, mineral fuels or coal. The volume of tailings is normally far in excess of the liberated resource, and the tailings often contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
254
0
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(331 citation statements)
references
References 109 publications
3
254
0
26
Order By: Relevance
“…As a matter of fact, due to the natural disasters and/ or extreme weather events, several dam failures and catastrophes of tailings release have occurred over the past years. According to the United Nations Environment Program (UNEP) and International Commission on Large Dams (ICOLD) [6,7], the main reasons for these failures and events are the inadequate regulation of water balance and tailings deposition homogeneousness, the absence of advanced tailings dam construction methods and the lack of safe operations. In October 2010, substantial widespread farmland and water were polluted by an unparalleled disastrous release of ~0.7 million m 3 of red slurry in Ajka, Hungary [8].…”
Section: Calamities Of Traditional Mine Tailings Storage Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, due to the natural disasters and/ or extreme weather events, several dam failures and catastrophes of tailings release have occurred over the past years. According to the United Nations Environment Program (UNEP) and International Commission on Large Dams (ICOLD) [6,7], the main reasons for these failures and events are the inadequate regulation of water balance and tailings deposition homogeneousness, the absence of advanced tailings dam construction methods and the lack of safe operations. In October 2010, substantial widespread farmland and water were polluted by an unparalleled disastrous release of ~0.7 million m 3 of red slurry in Ajka, Hungary [8].…”
Section: Calamities Of Traditional Mine Tailings Storage Facilitiesmentioning
confidence: 99%
“…Traditional mining tailings storage facilities have faced an enormous challenge to the treatment and disposal of tailings and require a multidisciplinary research, because the tailings can pollute environment by AMD and lead to tailings dam failures due to leakage, instability, liquefaction, and poor design [16,7]. Since the 1960s, 77 mining tailings dams have collapsed worldwide mainly because of the geotechnical instability, and caused at least 471 deaths as well as environmental destruction and serious economic impacts [17].…”
Section: Improvement Of Traditional Mining Tailings Storage Facilitiesmentioning
confidence: 99%
“…Their distribution process may be defined as active or passive. Active transformation occurs when the mining sediment transforms the river channel; for example, in the wake of a tailings dam spill (Kossoff et al, 2014). By contrast, passive dispersion occurs when mining-contaminated particulates are disseminated as part of the normal sediment load in the fluvial regime (Macklin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Breaches or failures to mine tailings storage facilities (TSF) are often catastrophic, impacting water and sediment quality, as well as aquatic life in rivers and lakes below the TSF (Azam and Li 2010;Kossoff et al 2014;Rico et al 2008). …”
Section: Historic Mine Tailings Breachesmentioning
confidence: 99%
“…The degree of contamination and the long-term impacts on the receiving aquatic system depend on four factors: the quality, quantity, and the rate of discharge of materials into receiving waters, and the effectiveness of the clean-up (Graf 1990;Macklin et al 2006). A review of historical TSF breaches by Kossoff et al (2014) indicated quantities of tailings released ranged from 100,000 -7,000,000 m 3 ; all of these are at least three times smaller than the estimated 25,000,000 m 3 released by the 2014 Mt Polley Mine TSF breach. Recently, there was a larger breach in Brazil in 2015 (Table 1.2).…”
Section: Impacts Of Mine Waste Spillsmentioning
confidence: 99%